THE EFFECT OF MULIA, AR-RUM, SHARIA-COMPLIANT BANK OF INDONESIA’S CERTIFICATE, INFLATION AND BI RATE ON SHARIA PAWNSHOP’S INCOME IN INDONESIA - Ade Sofyan Mulazid; Nina Astriana (I-Economics: A Research Journal on Islamic Economics)
This research aimed to analyze the effect of Mulia, Ar-Rum, Sharia-compliant Bank of Indonesia (sharia-compliant Bank of Indonesia)’s Certificate, Inflation and BI Rate on sharia pawnshop’s income in Indonesia during 2015-2017. Case study being the object of research was PT. Pegadaian (Persero). Secondary data derived from annual report published by Pegadaian (thereafter called Pawnshop). This study employed a multiple regression analysis method. The result of research showed that (1) Mulia financing affected significantly the income of Sharia pawnshop (thereafter, called Sharia pawnshop), (2) Ar-Rum Financing did not affect significantly the income of Sharia Pawnshop, (3) Sharia-compliant Bank of Indonesia’s Certificate did not affect significantly the income of Sharia pawnshop, and (4) inflation affected significantly the income of Sharia pawnshop and BI Rate affected Sharia pawnshop’s income significantly